Discovery of a non-toxic [1, 2, 4]triazolo[1, 5-a]pyrimidin-7-one (WS-10) that modulates ABCB1-mediated multidrug resistance (MDR). Issue 18 (1st October 2018) - Chang, Liming; Xiao, Mengwu; Yang, Linlin; Wang, Shuai; Wang, Sai-Qi; Bender, Andreas; Hu, Aixi; Chen, Zhe-Sheng; Yu, Bin; Liu, Hong-Min
Graphical abstract: Highlights: The nontoxic ABCB1 modulatorWS-10 was identified from our in-house molecular library. WS-10 selectively modulated ABCB1-mediated multidrug resistance. WS-10 enhanced the intracellular accumulation of Paclitaxel in SW620/Ad300 cells. The CETSA assay showed thatWS-10 could bind to ABCB1 protein. Abstract: Multidrug resistance (MDR) has been shown to reduce the effectiveness of chemotherapy. Strategies to overcoming MDR have been widely explored in the last decades, leading to a generation of numerous small molecules targeting ABC and MRP transporters. Among the ABC family, ABCB1 plays key roles in the development of drug resistance and is the most well studied. In this work, we report the discovery of a non-toxic [1, 2, 4]triazolo[1, 5- a ]pyrimidin-7-one (WS-10 ) from our structurally diverse in-house compound collection that selectively modulates ABCB1-mediated multidrug resistance.WS-10 enhanced the intracellular accumulation of paclitaxel in SW620/Ad300 cells, but did not affect the expression of ABCB1 Protein and ABCB1 localization. The cellular thermal shift assay (CETSA) showed thatWS-10 was able to bind to ABCB1, which could be responsible for the reversal effect ofWS-10 toward paclitaxel and doxorubicin in SW620/Ad300 cells. Docking simulations were performed to show the possible binding modes ofWS-10 within ABCB1 transporter. To conclude, WS-10 could be used as a template for designing new ABCB1 modulators to overcome ABCB1-mediated multidrug resistance.